An explorative vs. traditional practical course: how to inspire scientific thinking in medical students - Eckel, Julia; Zavaritskaya, Olga; Schüttpelz-Brauns, Katrin; Schubert, Rudolf (Advances in physiology education, 2019)
Recently, medical students’ scientific thinking skills have been identified as an important issue in medical education. Scientific thinking cannot be imparted in conventional lectures, but rather requires actively involving students. We modified a practical course in physiology. A study was designed to test whether the new course fosters scientific thinking without impairing the transfer of physiological knowledge. The study group consisted of 226 first-year medical students at the Medical Faculty Mannheim of Heidelberg University. Written consent to participate in the study was obtained from all participants. The group was then randomly divided into two groups (traditional vs. modified course). The subject of both courses was a laboratory experiment in skeletal muscle physiology. In the traditional course, the students addressed topics already presented in lectures. In the modified course, students dealt with the same topics as in the traditional course, but the experiment was expanded to include one issue not taught before. When working on this issue, the students were instructed in scientific thinking. All participants filled out a questionnaire with 15 multiple-choice questions addressing the physiological subject matter and four open-ended questions addressing the criteria of scientific methodology. Physiological knowledge in both groups did not differ [F(1) = 2.08, P = 0.15]. Scores in scientific thinking in the modified course were higher (mean = 4.20, SD = 1.89) than in the traditional course (mean = 2.04, SD = 1.91) with F(1) = 70.69, P < 0.001, η2 = 0.24 (large effect). Our study demonstrates that small adjustments to courses in medical education can promote scientific thinking without impairing knowledge transfer.